General-Compulsory Medical Insurance: World Experience - YAROSHENKO, Oleg M.; VAPNYARCHUK, Natalya M.; LOZOVOI, Sergii V.; YAKOVLEVA, Galina O.; YAKOVLYEV, Oleksandr A. (Journal of Advanced Research in Law and Economics; Vol 9 No 5 (2018): JARLE Volume IX Issue 5(35) Fall 2018DO - 10.14505//jarle.v9.5(35).38, 2018)
Given the insufficient level of regulation of the health insurance institute in Ukrainian legislation, the article attempts to investigate global experience in the context of this issue. In particular, a number of international documents were investigated, their content was characterized and the main provisions were highlighted. Based on collected and analyzed data, the authors outlined the areas of adaptation of Ukrainian legislation to the highest standards of the EU, made a proposal for the ratification of the conventions of the International Labor Organization. Supported a proposal for the development and adoption of a separate special law on general-compulsory state health insurance, which would regulate issues related to health insurance.